Academic mobility of doctoral students in Brazil: An analysis based on Lattes Platform - Mascarenhas, Higor; Rodrigues Dias, Thiago Magela; Dias, Patrícia (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. In this article, the academic mobility of Brazilian doctoral students moving from their home cities to other Brazilian cities including other countries is examined. Design/Methodology/Approach. The LattesDataXplorer tool was used to extract curriculum data from the Lattes Platform. 308,317 resumes were collected in May 2019, since then the data have been filtered, obtaining relevant data for the research. After extracting the data, they were enriched with the integration of other data sources, thus enabling the characterization of bibliometric networks for the analyses. Results/Discussion. It was possible to measure distances traveled by Brazilian doctors throughout their academic training, as well as to point out the cities, states, and countries whose doctors most meet in the academic journey and the relationships between these locations. Thus, making it possible to obtain a portrait of how the Brazilian scientific exodus occurs. In general, more than 90% of curricula have information on the academic background at each level of education. The average distance of 291 km between birth and place of formation at the graduation level is strongly influenced by outliers. Individuals choose to travel shorter distances throughout the academic training process, being the geographic location a strong influence on the migratory process for training. Conclusions. The United States represents the country where individuals choose to move the most. Regarding international migration, there is more preference for European countries than South American ones. When it comes to intra-regional migration, students prefer those states where the most relevant universities are located. Originality/Value. The article presents the results of original research focusing on the Brazilian scientific community. Distances performed by doctoral students throughout their academic trajectory are measured, as well as the main locations where they tend to move.